The Effect of Economic Value Added (EVA) and Return on Assets (ROA) on Stock Returns - Lita Sonia (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Financial information on companies that go public is useful for investors as a basis for evaluating a company to make investment choices. One of the aspects that will be assessed by investors is financial performance. Recently, a new approach has been developed in measuring performance known as Economic Value Added (EVA). and Return On Assets (ROA). This study aims to determine the effect of Economic Value Added and Return On Assets on Stock Returns in the companies sub-sector of beauty and household needs. This study uses a non-probability sample because the company’s income statement and balance sheet are incomplete. Data collection was performed using internet hard reset library research and journals. Statistical methods use multiple linear regression with hypothesis testing partial statistical tests ( t-test) and simultaneous tests (f-test). The result of this indicates that the Economic Value Added partiality influences Stock Return and Return On Assets does not affect the Stock return. This is indicated by the calculated t-value of variable X1= sig 0,024, X2= t-value 2,713 partially no effect on stock returns. While simultaneously obtained the calculated f-value of 3,936. This the obtained that Economic Value Added and Return On Assets simultaneously effect on Stock Returns.